(untitled) (Scottish Historical and Archaeological Internet Reports, 2009)
The term ’stack’ is difficult to define, but usually refers to an isolated pinnacle of rock entirely surrounded by the sea at high tide. If a summit has a larger diameter than its height, then it is an island. Many of the sites in this project are islands or promontories, despite being described as stacks by their place names. A brief account of geological formation is followed by a table which lists all the known sites.